In vitro biopharmaceutic evaluation of capsules containing fluconazole (Revista Brasileira de Ciências Farmacêuticas, 2002)
Many brazilian pharmaceutical industries manufacture capsules containing 150 mg of the antifungal agent fluconazole. The present study was designed to perform a in vitro biopharmaceutical evaluation of three commercial products available in Brazil, designated as products A, B and C. After a dissolution method was developed and standardized, the dissolution kinetics for samples of two batches of each product was analysed through k s (dissolution rate constant) and t85% (time for dissolution of 85% of the drug in the dosage form), obtained from dissolution profiles. Results showed k s values of 0,1377 min-1 and 0,1079 min-1 for the tested batches of A, 0,5421min-1 for the tested batches of B and 0,0354 min-1 and 0,0146 min-1 for the tested batches of C. t85% was 15,09 min e 20,06 min for the tested batches of A, 5,64 min and 6,02 min for the tested batches of B and 132,12 min and 56,05 min for the tested batches of C. It was concluded that the dissolution of fluconazole in capsules follows first order kinetics for the three products and product B shows the greatest dissolution rate, followed by products A and C.